2016
DOI: 10.1007/s00779-016-0936-6
|View full text |Cite
|
Sign up to set email alerts
|

Do-it-yourself services and work-like chores: on civic duties and digital public services

Abstract: Doing civic duties is neither paid work nor leisure: it is a private, work-like activity. Digital services enrol customers in doing work tasks. Also digital public services delegate work to citizens, but there are important differences between automation for citizens doing their civic duties and services that customers choose to use. In this paper, we discuss how digitally automated services remove some tasks but also introduce new work tasks for citizens and how citizens handle these. We present a study of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
(74 reference statements)
1
17
0
5
Order By: Relevance
“…In conclusion, this paper presents a rich picture of the practices of a cohort of men and women in knowledge-intensive roles as they develop and deploy strategies and boundaries for dealing with work and non-work. The paper contributes to CSCW in 2 ways: firstly some of our findings significantly add to those from previous research that they resonate with, via novel and nuanced empirical material, particularly about boundaries as resources (Bødker 2016), variability of individual strategies and their match to personal circumstances (Gray et al 2016), complex motivations underpinning one's strategies (De Carvalho et al 2017;Jarrahi and Sawyer 2017), and the labour-intensive nature of personal tasks (Verne and Bratteteig 2016). Secondly, we have presented novel findings that charter new territory for future CSCW research on the technological mediation of work/life practices that we summarise below.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In conclusion, this paper presents a rich picture of the practices of a cohort of men and women in knowledge-intensive roles as they develop and deploy strategies and boundaries for dealing with work and non-work. The paper contributes to CSCW in 2 ways: firstly some of our findings significantly add to those from previous research that they resonate with, via novel and nuanced empirical material, particularly about boundaries as resources (Bødker 2016), variability of individual strategies and their match to personal circumstances (Gray et al 2016), complex motivations underpinning one's strategies (De Carvalho et al 2017;Jarrahi and Sawyer 2017), and the labour-intensive nature of personal tasks (Verne and Bratteteig 2016). Secondly, we have presented novel findings that charter new territory for future CSCW research on the technological mediation of work/life practices that we summarise below.…”
Section: Discussionsupporting
confidence: 60%
“…These findings about blurring life into work particularly add to a body of research that has identified how digital technologies aid tasks that might not be part of paid employment, but are labour-intensive and require quasi-professional skills (such as healthcare management, accounting and taxes, etc., see for example Verne and Bratteteig 2016). Additionally, we have seen in our participants' cohort how work time and spaces can become pervaded by non-work aspects of life and therefore that they constantly make decisions about setting up or dissolving boundaries keeping life from spilling into work.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, relatively few studies have examined the work of street-level bureaucrats in social service agencies. For examples, Borchorst and Bødker (2011) examine how citizens share information with governmental offices, and Breit and Salomon (2014) and Verne and Bratteteig (2016) examine the impact of digitalization on public service encounters. Borchorst et al, (2012) found out that the stronger the citizens' ability to perform identities that are compatible with the bureaucratic administrative process, the greater quality and swiftness the service.…”
Section: Social Welfare and Public Servicementioning
confidence: 99%
“…A study of early computational systems in social security offices (Snellen and Wyatt, 1993), have argued that such systems increase focus on bureaucratization and public administration, and reduce focus on citizens. More recent studies of public services suggest the design of systems that move away from lean and rational case processing, applying a citizens-centric perspective (Verne and Bratteteig, 2016). and improving citizen involvement in the configuration of service provision (e.g., supporting transparent and accessible understanding of the case processes, and including the rationale behind particular decisions) (Borchorst and Bødker, 2011).…”
Section: Technologies' Impact On Welfare Workersmentioning
confidence: 99%